2010
DOI: 10.1002/app.32734
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of uranyl ions from aqueous solutions using crosslinked maleic anhydride‐octene‐styrene terpolymer

Abstract: Maleic anhydride-octene-styrene terpolymer has been modified with allylic alcohol and methylmethacrylate to prepare a new crosslinked functional polymer sorbent. The sorption behaviors of uranyl ions on the optimum sorption conditions were determined. The synthesized crosslinked polymer sorbent has a network structure and contains carboxylic acid, carbonyl, and ester groups, all of which are capable of interacting with metal ions. The maximum experimental sorption capacity of the sorbent for uranyl ions has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…Ion imprinted hydrogels were developed by Yunhai Liu et al by using hydrogel membranes of chitosan/poly(vinyl alcohol) and reported the max adsorption capacity of 156 mg.g − 1 . Acrylic terpolymer based montmorillonite nano composite hydrogels were developed by Akperov et al and maximum adsorption reported was 165 mg.g − 1 . Cellulose triacetate membranes with activated carbon reported that max adsorption capacity is 57.33 mg.g − 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Ion imprinted hydrogels were developed by Yunhai Liu et al by using hydrogel membranes of chitosan/poly(vinyl alcohol) and reported the max adsorption capacity of 156 mg.g − 1 . Acrylic terpolymer based montmorillonite nano composite hydrogels were developed by Akperov et al and maximum adsorption reported was 165 mg.g − 1 . Cellulose triacetate membranes with activated carbon reported that max adsorption capacity is 57.33 mg.g − 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Maleik anhidridard-stiren kopolimeri, MA ile S'den benzende serbest radikal polimerleştirmesi ile daha önceki çalışmamızda ayrıntıları verildiği biçimde sentezlenmiştir [7]. Uranil nitratın (UO2(NO3)2.6H2O) sulu çözeltisinden uranil iyonlarının tutulmasına uranil iyon derişimi, ortam sıcaklığı ve madde boyutunun etkisi incelenmiştir.…”
Section: Introductionunclassified
“…Bu çalışmada adsorbent olarak kullanılmak üzere, maleik anhidrid (MA) ile stiren (S)'den serbest radikal polimerleştirmesi ile hazırlanmış ve bu maleik anhidrid-ard-stiren (MA/S) kopolimerleri kullanılarak uranil iyonlarının sulu çözeltiden adsorpsiyonunun incelenmesi amaçlanmıştır. Maleik anhidridard-stiren kopolimeri, MA ile S'den benzende serbest radikal polimerleştirmesi ile daha önceki çalışmamızda ayrıntıları verildiği biçimde sentezlenmiştir [7]. Uranil nitratın (UO2(NO3)2.6H2O) sulu çözeltisinden uranil iyonlarının tutulmasına uranil iyon derişimi, ortam sıcaklığı ve madde boyutunun etkisi incelenmiştir.…”
Section: Introductionunclassified
“…Wastewater containing heavy metals is generated as untreated or partially treated by‐products of various industries and enters into public sewers, rivers, the sea and land. The important toxic metals are Cd, Zn, Pb, Ni, Cr, UO 2 and Hg, which enter into water bodies through wastewater discharged by industries . This has resulted in severe contamination of ground and surface water.…”
Section: Introductionmentioning
confidence: 99%